Ugochukwu, Oliver Ukachi - Maduabuchi , Patrick Aja; Chukwu, Chinecherem Adanna; Okechukwu, Ugwu Paul Chima; Anthony, Boniface Ale; Chinedu , Peter Agu; Deusdedi, Tusubira; Chukwu, Darlington C; Onyedika, Gabriel Ani; Ugbala, Ezebuilo Ekpono; Akobi , Hilary Ogwoni; Awoke , Joshua Nonso; Ogbu, Patience N; et al. (Oxford University Press, 2024)
OBJECTIVES: This study looked at how CMSO affected male Wistar albino rats' liver damage caused by bisphenol A. METHODS: The standard HPLC method was used to assess the CMSO's phenolic content. Then, six (n = 8) groups of forty-eight (48) male Wistar rats (150 20 g) each received either CMSO or olive oil before being exposed to BPA for 42 days. Groups: A (one milliliter of olive oil, regardless of weight), B (BPA 100 mg/kg body weight (BW)), C (CMSO 7.5 mg/kg BW), D (CMSO 7.5 mg/kg BW + BPA 100 mg/kg BW), E (CMSO 5.0 mg/kg BW + BPA 100 mg/kg BW), and F (CMSO 2.5 mg/kg BW + BPA 100 mg/kg BW). KEY FINDINGS: A surprising abundance of flavonoids, totaling 17.8006 10.95 g/100 g, were found in the HPLC data. Malondialdehyde, liver enzymes, reactive oxygen species, total bilirubin, and direct bilirubin levels were all significantly elevated by BPA (p 0.05). Additionally, nuclear factor-B, interleukin-6, interleukin-1, tumor necrosis factor, and histological alterations were all considerably (p 0.05) caused by BPA. The altered biochemical markers and histology were, however, noticeably recovered by CMSO to a level that was comparable to the control. CONCLUSION: Due to the abundance of flavonoid components in the oil, CMSO protects the liver from BPA-induced hepatotoxicity by lowering oxidative stress and inflammatory reactions